1996
DOI: 10.1002/(sici)1096-9861(19960617)370:1<71::aid-cne7>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and steroid hormone regulation of aromatase mRNA expression in the forebrain of adult male and female rats: A cellular-level analysis using in situ hybridization

Abstract: Many of the effects of gonadal steroid hormones in the male brain are due to the actions of the testosterone metabolite estradiol, which is synthesized by the actions of the P450 enzyme aromatase. Aromatase activity is present in regions of the preoptic area, hypothalamus, and limbic system. Levels of aromatase activity in the brain are highly dependent on gonadal steroid hormones in many brain regions, but not all. We examined the distribution of aromatase mRNA in adult male and female rat brains as well as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
51
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 118 publications
(62 citation statements)
references
References 42 publications
9
51
2
Order By: Relevance
“…In addition, AROM expression has been reported in regions that are not directly involved in the regulation of reproductive behavior, such as the hippocampus (Wehrenberg et al, 2001;Hojo et al, 2004;Bender et al, 2010), the neocortex (MacLusky et al, 1994;Yague et al, 2006Yague et al, , 2008, and, as also shown here, the central and basolateral amygdala (Sanghera et al, 1991;Wagner and Morrell, 1996;Horvath et al, 1997;Roselli et al, 1998;. This suggests that the functions of AROM in the brain are not limited to reproduction, but extend to mood, affective behaviors, and memory formation.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…In addition, AROM expression has been reported in regions that are not directly involved in the regulation of reproductive behavior, such as the hippocampus (Wehrenberg et al, 2001;Hojo et al, 2004;Bender et al, 2010), the neocortex (MacLusky et al, 1994;Yague et al, 2006Yague et al, , 2008, and, as also shown here, the central and basolateral amygdala (Sanghera et al, 1991;Wagner and Morrell, 1996;Horvath et al, 1997;Roselli et al, 1998;. This suggests that the functions of AROM in the brain are not limited to reproduction, but extend to mood, affective behaviors, and memory formation.…”
Section: Discussionmentioning
confidence: 56%
“…In addition to the hippocampus, the amygdala is a brain region rich in AROM (Balthazart et al, 1991;Sanghera et al, 1991;Shinoda et al, 1994;Wagner and Morrell, 1996;Horvath et al, 1997;Roselli et al, 1998;. Anatomically, the amygdala comprises approximately a dozen nuclei that are developmentally derived from both pallial and subpallial sources (Swanson and Petrovich, 1998;Puelles et al, 2000;LeDoux, 2007).…”
Section: ؉mentioning
confidence: 99%
“…The similar effects of T and E2 on basal nociception and morphine antinociception may be due to the aromatization of T to E2. Like male rats, females convert T to E2 via aromatase in the brain, though to a lesser extent than do males (Wagner and Morrell, 1996;Roselli and Resko, 1997). However, if the effects of T on basal nociception and morphine antinociception were actually due to E2, then the limited lordosis and uterine weights, and failure to show any proestrus or estrus stages based on vaginal cytology suggest that considerably less E2 is necessary to produce changes in nociception and morphine antinociception than is necessary to fully reinstate reproductive capabilities.…”
Section: Effects Of Gonadal Steroid Manipulations In Femalesmentioning
confidence: 99%
“…The VMHvl and VMHdm contain high concentrations of steroid receptor mRNAs, and are the most studied of the four subdivisions (Simerly, et al, 1990;Wagner and Morrell, 1996). For example, the VMHdm appears to be critical for the expression of ultrasonic vocalization and scent marking behaviors in males (Yahr and Greene, 1992;Flanagan-Cato et al, 2001;Harding and McGinnis, 2005).…”
Section: Introductionmentioning
confidence: 99%